Evaluating Medical Students' Knowledge of Medical Malpractice: A Pilot Study - Nikkhahmanesh, Nia; Kang, Paul; vanSonnenberg, Eric (International Journal of Medical Students, 2023)
Introduction: Although medical malpractice lawsuits are common and have a tremendous financial and psychological impact on physicians, education about medical malpractice is almost non-existent in most medical school curricula around the world. Nonetheless, medical students are concerned about looming legal lawsuits during their careers and have expressed desire to become educated. The objective of the present study is to evaluate and gauge baseline medico-legal knowledge of medical students. Methods: A survey with 25 multiple-choice quiz questions regarding malpractice risks, standards of care, and malpractice premiums was prepared with information obtained from peer-reviewed articles after a thorough literature review failed to produce a validated questionnaire for medical students. The survey was distributed to medical students across 5 consecutive years at our medical school, totaling 420 students. Data from the survey was collected via Qualtrics before undergoing statistical analysis. Results: The completion rate for the survey was 110/420 (26.2%). The results showed that no group of students scored greater than 50% correct on the survey, with an overall median score of 40% correct for all students combined. Fourth year medical students correctly answered 1.77 more questions, on average, than first year medical students. There were no statistically significant differences in survey score between students with a personal or familial medical malpractice involvement. Discussion: The results are an indication that students are not well-educated about medical malpractice, and that medical malpractice education should be implemented in medical school to help prepare future physicians to protect their patients and hopefully avoid malpractice lawsuits.